Gourmet grasshopper - Abdul Karim, Muhammad Shahrim; Abdul Halim, Nurhasmilaalisa; Mohamad Aris, Mohamed Haidrin; Abu Bakar, Ainul Zakiah (Universiti Putra Malaysia Press, 2013)
Grasshopper has been long accepted as an exotic food by many countries in the Southeast Asian region especially Thailand, Vietnam, Cambodia, Laos, Myanmar, Philippines and Indonesia. In the case of Malaysia, traditionally, grasshoppers particularly belalang padi is quite popular among the local farmers most notably at the countryside, where the grasshopper can be eaten raw, sun-dried, fried, flavoured with spices, and used in soups or as fillings for various dishes. In line with the increasing trend of introducing insects in high-end dining restaurant in the Western culinary world, restaurants in Malaysia has put an effort to introduce stylish and chic feast from grasshopper as a fusion culinary feature.